Using MRI to elucidate the importance of physical activity to brain health and motor function in ageing - Nicholas, Rosemary (2023)
We live in an increasingly ageing population where people are living longer, but quality of life is not keeping up with increased lifespan. Concerns contributing to poor health in ageing include cognitive impairment and frailty driven by neurodegeneration and declining musculoskeletal health. Inactivity is also a significant driver of poor health in ageing and this may divulge important mechanisms of age-related decline. This thesis aims to differentiate whether activity in ageing impacts on physiological responses by studying trained and untrained individuals.